2013
DOI: 10.1161/hypertensionaha.111.01076
|View full text |Cite
|
Sign up to set email alerts
|

Human β-Defensin 2 Is a Novel Opener of Ca 2+ -Activated Potassium Channels and Induces Vasodilation and Hypotension in Monkeys

Abstract: Human β-defensin 2 (HBD2) is a cysteine-rich cationic antimicrobial peptide known for its important role in innate immune system. Intensive studies have demonstrated its antimicrobial and chemotactic activities in vitro. In this study, ELISA analysis showed that HBD2 was significantly downregulated in sera of patients with hypertension. It relaxed vessel smooth muscle by acting on the major regulatory pathways, contributing to vessel smooth muscle contraction. Electrophysiology analysis indicated that HBD2 act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 23 publications
0
16
0
2
Order By: Relevance
“…Recently, hBD2 was predicted to be an inhibitor of rat Kv1.2 channel by computational docking [10], and found to be a novel opener via interacting with human b1 subunit coexpressed with mouse a subunit of large conductance Ca 2? -activated potassium channel [11]. In this work, the in-depth structural analysis indicated that hBD2 and different Kv1.3 channel-blocking toxins are basic peptides while they are also structurally constrained by several disulfide bridges [2,12].…”
Section: Introductionmentioning
confidence: 72%
“…Recently, hBD2 was predicted to be an inhibitor of rat Kv1.2 channel by computational docking [10], and found to be a novel opener via interacting with human b1 subunit coexpressed with mouse a subunit of large conductance Ca 2? -activated potassium channel [11]. In this work, the in-depth structural analysis indicated that hBD2 and different Kv1.3 channel-blocking toxins are basic peptides while they are also structurally constrained by several disulfide bridges [2,12].…”
Section: Introductionmentioning
confidence: 72%
“…A recent study reported that bis-(1,3-dibutylbarbituricacid)trimethine oxonol [DiBAC4(3)] and N -arylbenzamide can activate the BK channel in β1 subunit dependence, but DiBAC4(3) partially blocked the BKα/β2 channel’s currents (Kirby, Martelli, Calderone, McKay, & Lawson, 2013; Morimoto et al, 2007). Additionally, HBD2 (human β-defensin 2) could activate BK channels via interactions with Leu41 and Gln43 of the β1 extracellular loop (Liu et al, 2013). A recent report showed that the newly identified BK channel opener GoSlo-SR-5-130, but not its analogue GoSlo-SR-5-6, required the presence of β1 or β4 subunit to achieve its the maximal modulatory effects on BK channels (Large et al, 2015).…”
Section: Modulation Of the Bk Channel's Pharmacological Propertiesmentioning
confidence: 99%
“…ML277 activated the channel and nearly doubled the current size and the total conductance ( Figures 1A and 2A). Interestingly, unlike other activators that potentiate ion channel currents by left-shifting the G-V relationship (De Silva et al, 2018;Gao et al, 2017;Guo et al, 2017;Liu et al, 2013;Seebohm et al, 2003a;Zheng et al, 2012), ML277 slightly shifted the G-V relationship of KCNQ1 channels to more positive voltages (ΔV~ 6 mV, Figure 2B,C). This curious result can be explained by properties of KCNQ1 voltage-dependent activation process.…”
Section: Ml277 Right Shifts the G-v Relationship Of Kcnq1 Channelsmentioning
confidence: 72%